Моніторинг та вимірювання у ISO 14001 - Юношев, Д. Є. (ХНУРЕ, 2021)
After the introduction of the new version of ISO 14001, it became necessary to change the rules for use of the standard. The version of ISO 14001:2015 removes the mandatory requirement for full monitoring of locations where significant environmental impacts exist or may exist. To do so, consider what the standard itself proposes and the need to documenting monitoring and measurement in ISO 14001.